No difference in stroke knowledge between Korean adherents to traditional and western medicine – the AGE study: an epidemiological study - Eun Su-Yong; Kim Eunkyung; Jo Inho; Jo Sangmee; Park Moon Ho; Han Changsu; Park Min Kyu (BMC Public Health, 2006)
Abstract Background Effective stroke intervention and risk reduction depend on the general public's awareness and knowledge of stroke. In Korea, where both traditional Oriental medicine and Western medicine are practiced, estimates of the general public's awareness and knowledge of stroke are poor. The present study sought to describe the inception cohort of the Ansan Geriatric Study (AGE study) and to determine baseline stroke awareness and preferred medical treatment for stroke in this Korean sample. Methods A total of 2,767 subjects selected randomly from the Ansan Geriatric Study in South Korea were questioned about stroke. Their answers were compared with their sociodemographic data and other variables. Results Only 44.8% of participants correctly identified stroke as a vascular disease in the human brain. Sudden numbness or weakness was the most frequently identified stroke warning sign (60.2%). Hypertension (66.7%) and mental stress (62.2%) were most frequently identified as stroke risk factors. The contributions of diabetes mellitus and cardiovascular disease to stroke were underestimated; they were identified as risk factors by 28.3% and 18.6% of participants, respectively. The predictors for poor knowledge of stroke warning signs and risk factors were similar irrespective of preference for Western or Oriental medical treatment, and included those with lower levels of education and inaccurate definition of stroke. Television and radio (40.3%) were the most frequent sources of stroke information for both groups. Conclusion This study shows that knowledge of stroke is similar among Koreans with preferences for either Western or Oriental medical treatment and that misunderstandings about stroke are common among the Korean elderly. In order to prevent and manage stroke effectively, public health education regarding basic concepts of stroke is necessary. This should target those with a lower level of education and a misunderstanding of the definition of stroke.